Foliations of codimension one and Milnor's conjecture - Bolotov, D.V. (Журнал математической физики, анализа, геометрии, 2018)
We prove that a fundamental group of leaves of a codimension one C²- foliation with nonnegative Ricci curvature on a closed Riemannian manifold is finitely generated and almost Abelian, i.e., it contains finitely generated Abelian subgroup of finite index. In particular, we confirm the Milnor conjecture for manifolds which are leaves of a codimension one foliation with nonnegative Ricci curvature on a closed Riemannian manifold. Ми доводимо, що фундаментальна група шарiв C²-шарування ковимiрностi один невiд'ємно кривини Рiччi замкнутого рiманова многовиду є скiнченно породженою та майже абелевою, тобто мiстить скiнченно породжену абелеву пiдгрупу скiнченного iндексу. Зокрема, ми пiдтверджуємо гiпотезу Мiлнора щодо многовидiв, якi є шарами шарування ковимiрностi один невiд'ємно кривини Рiччi замкнутого рiманова многовиду.